APLIKASI TEKNOLOGI BUDIDAYA RAMAH LINGKUNGAN TERHADAP KUALITAS BUAH STROBERI - Sumayku, Bertje R.A.; Wardiyati, Tatik; Afandhi, Aminudin; Polii-Mandang, Jeanny (EUGENIA, 2017)
ABSTRACT Â  This study aimed to compare the application of environment-friendly cultivation technology on the quality of strawberries. The experimental design using a factorial in a randomized block design (RAK), with 2 factors, namely: 1). Farmers treatment technology that chicken manure 20 t / ha + Urine Rabbits 1: 5 liters of water; 2). Treatment T. koningii 15 g / kg of soil in chicken manure 5 tons / ha). Data were analyzed by t test statistics, if different continued with test Duncun at 0.05. Research results show that treatment of PP (T. koningii Technology) has Vitamin C is 27.1 mg / 100g, higher than the Treatment PT (Technology Farmers) is 22.5 mg / 100g. The vitamin C content of the variables were not significantly different between treatments, while the variable texture of the fruit, and sugar content were significantly different. Keywords: applications agriculture environmentally-friendly, strawberry fruit quality